Imaging diagnosis and treatment results of arteriovenous fistulas stenosis complication among hemodialysis patients - Pham, Hien Van; Tran, Nhat Van; Van, Quang Nguyen; Tran, Huong Thi Bich (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Introduction: Percutaneous transluminal angioplasty (PTA) presents several advantages in addressing arteriovenous fistula (AVF) stenosis compared to surgical approaches. In addition, Doppler ultrasonography (DUS) serves as a noninvasive technique for stenosis measurement and access flow volume calculation. This study aimed to evaluate the agreement in stenosis diagnosis using PTA and DUS before intervention and to assess the effectiveness of the PTA method after intervention. Method: A non - controlled intervention study involved 15 chronic HD patients with a mature AVF in place for over three months, presenting AVF stenosis ≥ 50%, who underwent PTA intervention. Correlation analysis was employed to assess the similarity of AVF stenosis evaluations using DUS and PTA. The study also compared pre - and post - intervention indicators to evaluate the effectiveness of PTA intervention. Results: The results indicated a strong positive correlation between the two techniques (r = 0.997, r2 = 0.994, p < 0.001). Following intervention, all patients were considered successful, with significant reductions observed in various indicators, including alterations in murmurs along AVF, VAPR, the number of patients with AVF stenosis ≥ 50% on DUS, and none with Qmin < 500 mL/min. Conclusion: This study recommends utilizing DUS to evaluate stenosis before contemplating PTA intervention, owing to the correlation and similarity observed in the results of AVF stenosis examination between these two techniques. Ultimately, our research endorses PTA intervention as the preferred method for HD patients with AVF stenosis, considering the observed enhancements in clinical, hemodialysis, and DUS parameters.